Public and private sector wages interactions in a general equilibrium model - Fernández-de-Córdoba, Gonzalo; Pérez, Javier J.; Torres, José L. (Frankfurt am Main, 2009)
"This paper develops a dynamic general equilibrium model in which the public and the private sector interact in the labor market. Previous studies that analyze the labor market effects of public sector employment and wages have mostly assumed exogenous rules for public wage and public employment. We show that theories that equalize wages with marginal products in the private sector can rationalize the interaction of public and private sector wages when extended to accommodate a non-trivial government sector/public sector union that endogenously determines public employment and wages. Our model suggests a positive correlation between public and private sector wages. Any increase in tax revenues, coupled with the existence of a positive public-private sector wage gap, makes working in the public sector an attractive option. Thus, a positive neutral productivity shock increases public and private sector wages. More interestingly, even a private-sector specific productivity shock spills-over to the public sector, increasing public wages. These facts lend some support to the wage leading role of the private sector. Nevertheless, at the same time, a positive shock to public sector wages would lead to an increase in private sector wages, via the flow of workers from the private to the public sector."